2007
DOI: 10.1097/aia.0b013e31803419c3
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Insulin Signaling as a Potential Trigger of Pain in Diabetes and Prediabetes

Abstract: Chronic sensorimotor distal symmetric polyneuropathy (DPN) is a common neurologic complication of diabetes mellitus. Prevalence of DPN approaches 50% in people living with diabetes, and about 10% of these cases are painful neuropathy. 1,2 Like other symptoms of DPN (loss of reflexes or somatic sensations), ''positive'' symptoms (pain and paresthesias) of DPN have symmetrical distribution and distal-toproximal progression. Nocturnal intensification seems to be another general characteristic of pain in DPN. 2 Ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The critical concentrations of plasma insulin required for maintenance of PPT and glucose are in the ranges of 1.5 – 2 ng/ml and 0.5 - 1 ng/ml, respectively (see Fig. 7 for random and (Dobretsov et al, 2007a) for fasting glucose data). The higher tolerance of glucose metabolism to insulinopenia than that of the PNS may derive from a combination of factors.…”
Section: Discussionmentioning
confidence: 99%
“…The critical concentrations of plasma insulin required for maintenance of PPT and glucose are in the ranges of 1.5 – 2 ng/ml and 0.5 - 1 ng/ml, respectively (see Fig. 7 for random and (Dobretsov et al, 2007a) for fasting glucose data). The higher tolerance of glucose metabolism to insulinopenia than that of the PNS may derive from a combination of factors.…”
Section: Discussionmentioning
confidence: 99%
“…Calcutt (36) has argued that some of these discrepancies may arise from testing methodology and the duration of diabetes. Dobretsov et al (37) have suggested that hyperalgesia may relate better to impaired insulin signaling than hyperglycemia. In the current study, despite a long-term end point (4 months), pain behavior had not disappeared in favor of simple sensory loss, despite significant but incomplete epidermal denervation.…”
Section: Discussionmentioning
confidence: 99%
“…5 In addition, there have been recent reviews in our specialty's symposium journals addressing mechanisms of chronic pain in the setting of diabetes. 6,7 Interestingly, these excellent reviews did not have any specific citations regarding the care of such patients receiving peripheral nerve blocks for surgical anesthesia-analgesia, presumably because such literature is sparse. There is animal evidence that nerve fibers of patients with diabetes may have a higher sensitivity to local anesthetics.…”
Section: Discussionmentioning
confidence: 99%